Immediate Self-Replantation of an Avulsed Tooth: 24-Month Follow-Up Case Report - Ayna, Buket; Atıcı, Elmas Tüfek; Aktürk, Ekin (Journal of Orofacial Research, 2018)
Avulsion is one of the most critical traumatic dental injuries. The prognosis of the treatment depends on the amount of vital periodontal fibrils and consequently the extraoral storage period, the storage medium, and the root development of the tooth. Immediate replantation is the most important factor for the prognosis. This case report presents the immediate self-replantation of an avulsed immature maxillary central incisor of an 8-year-old girl. Anamnesis disclosed that the tooth had been replanted within 5–10 minutes by the family. The teeth were splinted after extraoral, intraoral, and radiographic examinations had been performed. During 24 months of follow-up, positive results were obtained in examinations of the teeth. However, pulp canal obliteration (PCO) was observed in the maxillary left central incisor in the 12th month. PCO is regarded as the mechanism of healing of the pulp that occurs after replantation of avulsed teeth. However, follow-ups of the patient are continuing as recommended by the International Association for Dental Traumatology.